Schwann Cell-Specific Ablation of Laminin γ1 Causes Apoptosis and Prevents Proliferation - Yu, Wei-Ming (Society for Neuroscience, 2005)
To investigate the function of laminin in peripheral nerve development, we specifically disrupted the laminin γ1 gene in Schwann cells. Disruption of laminin γ1 gene expression resulted in depletion of all other laminin chains known to be expressed in Schwann cells. Schwann cells lacking laminin do not extend processes required for initiating axonal sorting and mediating axon-Schwann cell interaction. They fail to downregulate Oct-6 and arrest at the premyelinating stage. The impaired axon-Schwann cell interaction prevents phosphorylation of β-neuregulin-1 receptors and results in decreased cell proliferation. Postnatally, laminin-null Schwann cells exhibit reduced phosphatidylinositol 3 (PI3)-kinase activity and activation of caspase cascades, leading to apoptosis. Injection of a laminin peptide into mutant sciatic nerves partially restores PI3-kinase activity and reduces apoptotic signals. These results demonstrate the following: (1) that laminin initiates axonal sorting and mediates axon-Schwann cell interactions required for Schwann cell proliferation and differentiation, and (2) that laminin provides a PI3-kinase/Akt-mediated Schwann cell survival signal.